Improving teacher evaluation outcomes for special educators: what do the 'gatekeepers' say?. Issue 1 (15th August 2021) - Brobbey, Gordon; Kmail, Zaher
Abstract : Teacher evaluation has been at the forefront of accountability‐related reforms in the United States due to the realization that teacher effectiveness is a major contributor to student success. Data from evaluations have revealed vital insights into contributing factors to teacher effectiveness and generated valuable information for hiring, promotion, remuneration, and retention of teachers. Using existing evaluation systems to assess special educator performance, has, however, been challenging for a plethora of reasons, leading to disparate experiences for special educators. This study examined special educator knowledge of the process, perceptions about the applicability of existing teacher evaluation frameworks to their roles, responsibilities, and classroom contexts, as well as views about personal cost incurred. Findings reveal that special educators lacked deeper knowledge about the key components of evaluation systems and perceived the evaluation rubrics as impractical for their roles, responsibilities, and classroom contexts. The findings also reveal a strong preference for differentiated evaluation systems for special educators. Implications for practice, policy, and research are presented.